Tonsillar metastasis of nonsmall cell lung cancer with G719S mutation in exon 18: A case report. Issue 49 (December 2017) - Wu, Yimin; Zhu, Zhouyu; Chen, Yongyuan; Chai, Ying
Abstract: Rationale: Lung cancer has the highest mortality of all malignant tumors and is becoming the leading cause of death in China. Surgical resection is the best treatment for early non-small-cell lung carcinoma. But postoperative tumor recurrence is very common. Brain, bone and liver are the most common metastatic sites of lung cancer. Patient concerns: A 59-year-old woman was admitted to our hospital finding a lung nodule in physical examination. No other obvious symptoms were obsessed in this patient. No remarkable abnormality was detected in preoperative laboratory tests and physical examination. Diagnoses: A ground-glass nodule was detected on the left inferior lobe in the imaging examination. No metastases were detected before the surgery and early-stage lung cancer was supposed. Intervention: This patient underwent a radical resection of lung cancer successfully and enjoyed a peaceful postoperative rehabilitation. Outcomes: Although pathological diagnosed confirmed early stage lung adenocarcinoma (T1N0M0). The patient had tumor recurrence 7 months after operation. Gene sequencing confirmed the G719S mutation in exon 18 of the EGFR gene and target therapy, chemotherapy and radiotherapy were all given to this patient successively, but they were all unresponsive. The patient died 26 months after surgery. Lessons: We herein first report G719S mutation in lung adenocarcinoma with tonsillar metastasis. Generally, the tumor responded poorly to treatment and progressed quickly, which didn't achieve the desired effect. G719S mutant is supposed to be the cause of poor responsive to treatment.